Unicentric castleman's disease located in the lower extremity: a case report - Schweyer Stefan; Günnel Harald; Schaefer Inga-Marie; Korenkov Michael (BMC Cancer, 2011)
Abstract Background Castleman's disease is a rare form of localized lymph node hyperplasia of uncertain etiology. Although the mediastinum is the most common site of involvement, rare cases occurring in lymph node bearing tissue of other localization have been reported, including only a few intramuscular cases. Unicentric and multicentric Castleman's disease are being distinguished, the latter harboring an unfavorable prognosis. Case Presentation Here, we present a case of unicentric Castleman's disease in a 37-year-old woman without associated neoplastic, autoimmune or infectious diseases. The lesion was located in the femoral region of the right lower extremity and surgically resected after radiographic workup and excisional biopsy examinations. The tumor comprised lymphoid tissue with numerous germinal centers with central fibrosis, onion-skinning and rich interfollicular vascularization. CD23-positive follicular dendritic cells were detected in the germinal centers and numerous CD138-positive plasma cells in interfollicular areas. The diagnosis of mixed cellularity type Castleman's disease was established and the patient recovered well. Conclusions In conclusion, the differential diagnosis of Castleman's disease should be considered when evaluating a sharply demarcated, hypervascularized lymphatic tumor located in the extremities. However, the developmental etiology of Castleman's disease remains to be further examined.